Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.virol.2008.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Discordant varicella-zoster virus glycoprotein C expression and localization between cultured cells and human skin vesicles

Abstract: Because of its very low titer, varicella-zoster virus (VZV) infectivity is usually transferred by passage of trypsin dispersed infected cells. Previously, we observed that gC biosynthesis was markedly delayed in monolayers inoculated with cell free virus. In this report, we investigated the kinetics of gC expression in more detail and included studies of monolayers inoculated with trypsin dispersed infected cells, the more traditional method of VZV infection. Extensive imaging analyses disclosed that gC was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
6
23
0
Order By: Relevance
“…The low abundance of VZV gC protein in infected neurons was paralleled by low levels of true late VZV gC transcripts compared to transcription of the VZV IE62 gene and the early-late VZV gE gene in infected neurons, suggesting that low VZV gC abundance in infected neurons is due to a block in virus transcription rather than translation. Reduced transcription of VZV gC compared to that of VZV IE62 and VZV gE in neurons and fibroblasts is consistent with previous observations of reduced VZV gC transcription in human melanoma cells (8,19). While VZV gC production is significantly reduced in both virus-infected neurons and nonneuronal cells in tissue culture, VZV gC is nevertheless abundant in vesicles (20).…”
Section: Discussionsupporting
confidence: 91%
“…The low abundance of VZV gC protein in infected neurons was paralleled by low levels of true late VZV gC transcripts compared to transcription of the VZV IE62 gene and the early-late VZV gE gene in infected neurons, suggesting that low VZV gC abundance in infected neurons is due to a block in virus transcription rather than translation. Reduced transcription of VZV gC compared to that of VZV IE62 and VZV gE in neurons and fibroblasts is consistent with previous observations of reduced VZV gC transcription in human melanoma cells (8,19). While VZV gC production is significantly reduced in both virus-infected neurons and nonneuronal cells in tissue culture, VZV gC is nevertheless abundant in vesicles (20).…”
Section: Discussionsupporting
confidence: 91%
“…These values were 3.8-to 7.8-fold lower than that for pOka and 4.4-to 9-fold lower than that for the wild-type-like gB[Y920F] mutant. The ORF14 transcript is considered to be produced very late during VZV infection (41,42). This decrease is consistent with the poor propagation of the hyperfusogenic mutants.…”
Section: Resultssupporting
confidence: 54%
“…In both chicken pox and zoster, skin vesicles are the final site of VZV replication and virus formation. While the architecture of skin vesicles immunostained with a variety of anti-VZV antibodies has been previously delineated (41,49), the fact the zoster vesicles contain autophagosomes is an intriguing finding. The punctuate LC3B-positive autophagosomes were easily detected by confocal microscopy throughout the skin vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier report (49) we demonstrated that gE and gH were easily detected in vesicles. Recently, we documented that VZV gC was also expressed abundantly in skin vesicles, in contrast to the case for cultured cells (41). Skin vesicles were sectioned and labeled with a primary antibody against LC3B, followed by incubation with a fluorochrome-conjugated secondary antibody.…”
mentioning
confidence: 99%